ДОСЛІДЖЕННЯ СПОСОБІВ КЕРУВАННЯ ВЕНТИЛЬНО-ІНДУКТОРНИМ ПРИВОДОМ НАСОСНОГО ОБЛАДНАННЯ З ЦИКЛІЧНИМ НАВАНТАЖЕННЯМ - Мазуренко, Л.І.; Бібік, О.В.; Шихненко, М.О. (Інститут електродинаміки НАН України, Київ, 2022)
The electromechanical water supply system of a multi-storey building based on a switched reluctance motor is considered. A simulation model of the hydraulic network and criteria for evaluating the quasi-steady modes effectiveness of pumping equipment are given. A study of a centrifugal pump operational and energy characteristics has been carried out when adjusting its rotational speed to determine the frequencies at which the compliance of the pump pressure and flow with the hydraulic network requirements is ensured. Simulation models of control systems have been developed that provide the switched reluctance motor speeds at levels corresponding to specified flow rates of the hydraulic system pumping equipment, by means the phase voltage pulse-width regulation or the phase current limitation level adjustment. Comprehensive studies and comparative analysis of the switched reluctance centrifugal pump drive control principles were carried out according to the criteria for evaluating energy efficiency when regulating the rotational speed and changing the switching angles. As a result of this study, it was found that both pumping unit drive control principles provide its necessary productivity and are close in efficiency - a slightly higher efficiency can be achieved using the phase voltage pulse-width regulation of the switched reluctance motor with a changing the switching angles. References 10, figures 8.